2005
DOI: 10.1128/iai.73.2.695-702.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Imaging of Toxoplasma gondii Infection in Living Mice Reveals Dramatic Differences between Strains

Abstract: We examined the in vivo growth, dissemination, and reactivation of strains of the protozoan parasite Toxoplasma gondii using a bioluminescence-based imaging system. Two T. gondii strains, one with a highly virulent disease phenotype in mice (S23) and the other with a 1,000-fold-lower virulence phenotype (S22), were engineered to stably express the light-emitting protein luciferase. One clone of each wild-type strain was isolated, and the two clones (S23-luc7 and S22-luc2) were found to express similar levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 24 publications
5
168
0
1
Order By: Relevance
“…Monitoring by BLI of mice infected with H3F33 revealed that during the first days postinfection, R-Luc photon emission was localized mainly in the abdomen. This pattern is similar to that previously observed when mice were infected with tachyzoites expressing firefly luciferase (8,10,20,36). Autopsies carried out shortly after BLI analysis revealed that the signal was localized to the adipose tissue surrounding the ab- dominal organs.…”
Section: Discussionsupporting
confidence: 65%
“…Monitoring by BLI of mice infected with H3F33 revealed that during the first days postinfection, R-Luc photon emission was localized mainly in the abdomen. This pattern is similar to that previously observed when mice were infected with tachyzoites expressing firefly luciferase (8,10,20,36). Autopsies carried out shortly after BLI analysis revealed that the signal was localized to the adipose tissue surrounding the ab- dominal organs.…”
Section: Discussionsupporting
confidence: 65%
“…Even within T. gondii type, however, different clinical and behavioural outcomes may be predicted. Within Type II alone, variation in host cell gene expression Hill et al, 2012) and development (Diana et al, 2004), host immune and encephalitic response (Araujo and Slifer, 2003;Hill et al, 2012), parasite dissemination, reactivation and recrudescence (Saeij et al, 2005), and impact on host behaviour (Kannan et al, 2010) have all been reported between different strains. For example, whilst both Prugniaud (Pru) and ME49 have been reported to increase attraction to cat odour in mice at 2months post-infection, in at least one study this behaviour was no longer present with the ME49 strain at 7months (Kannan et al, 2010).…”
Section: What Parasite Strains Should Future Research Use and Why?mentioning
confidence: 99%
“…injection for 12 days. To monitor tissue burdens, mice were challenged with the luciferase expressing Pru-Luc strain and imaged as described previously 30 .…”
Section: Mouse Infectionsmentioning
confidence: 99%